Comparative Effectiveness of Betahistine vs Dimenhydrinate in Reducing Dizziness Handicap Scores in Patients with Peripheral Vestibular Disorders - Christin Rony Nayoan; Muyassaroh Muyassaroh; Zulfikar Naftali (RSUP Dr. Kariadi, 2025)
BACKGROUND: Peripheral vestibular disorder is a disorder of the peripheral vestibular system. Its symptoms affect the quality of life from moderate to severe. An objective assessment is quite difficult therefore a questionnaire method has been developed such as Dizziness Handicap Inventory (DHI). Aim of the treatment is to achieved optimal quality of life by using symptomatic treatment like dimenhydrinate and betahistine. AIMS : To prove the effectiveness of betahistine and dimenhydrinate and to compare the effectiveness in reducing DHI score METHOD : : This was an intervention study with pretest and posttest control group designs, randomized control trial, double blind study at ENT-HNS Clinic, CDC Dr. Kariadi Hospital and Dr.Soetrasno Hospital Rembang. Data was collected from September 2015 to June 2016. Subject filled out the DHI pre-test questionnaire, stratified randomly divided into 2 group. One group received betahistine 12 mg / 8 hours and the other received dimenhydrinate 50 mg / 8 hours in a double-blind selection process. After 2 weeks of drug administration, subject filled out a post test questionnaire of DHI. RESULT : Subjects were 44 people; dimenhydrinate, 20 people (45.5%) and betahistine, 24 people (54.4%). Result showed that DHI score of post test is lower than pre test in both group with significance value of p < 0.05. There is no significant difference in DHI score of dimenhydrinate compared with betahistine group (p = 0.137). CONCLUSION : Betahistine and dimenhydrinate are shown to be effective in lowering the DHI score.and betahistine not proven to be more effective